Liquidity Risk, Interconnectedness, and Investor Behavior in Investment Funds - Szabo, Milan; Brůna, Karel, 1973-; Novák, Jiří; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2024)
Funds' liquidity transformation is inevitable, yet it fundamentally contributes to systemic vulnerabilities arising from open-ended fund activities. The dissertation studies the factors amplifying liquidity risks in open-ended funds stemming from their structural liquidity mismatches. I study how these mismatches influence investors' and managers' behaviors. The dissertation also examines increasing interconnectedness due to cross-fund exposures and shows this may be related to the mismatch. The dissertation is a collection of four essays, each studying Czech open-end funds. The first essay explores inflows and outflows patterns in retail equity funds related to past and future performance. I find that retail investors become sensitive to bad performance in times of aggregate illiquidity and while investing in funds that hold more illiquid assets. Moreover, I document that when facing illiquidity and deteriorating performance, under-performing equity funds experience lower investor purchases and a larger share of redemption requests. I observe similar investor behaviour in periods when retail investors face constraints on their disposable income. The second essay explores liquidity management practices in bond and equity funds. I reconstruct funds’ cash flows to study liquidity transformation and liquidity management in investment funds. I study how portfolio illiquidity and current market conditions influence the joint behavior between investor redemptions and funds’ liquidity management. The third essay explores increasing funds’ investing in other funds. I study the implications of the growing interconnectedness. I show that cross-fund holdings boosted diversification and returns, albeit with increased volatility. I show that funds primarily sold fund shares compared to other assets to meet large redemptions and that funds increase sales of held funds experiencing investor outflows.
Finally, the study investigates supportive behavior within fund families. The fourth essay explores whether open-ended funds can amplify negative feedback loops of declining asset prices through procyclical selling and reduced purchases of securities experiencing falling prices. I reveal procyclical sales of government bonds and held fund shares. Furthermore, the study examines fund-related factors influencing procyclical sales. The results show that cyclical sales are intensified by the extent of funding constraints and liquidity mismatch.
Vedoucí práce: Karel Brůna
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: finance [obor disert. práce]; disertace; dissertations